Aromatherapy as an alternative of improvement in the quality of life of patients with breast cancer (2019)
We sought to identify the effects of the use of aromatherapy in patients with breast cancer. The Colombian validation questionnaire of the FACT-B scale was carried out to measure the quality of life of 35 patients with breast cancer of the Fundación Mujeres Por Tus Senos. Emotional state the item "I feel sad" in the pre-therapy survey 62% answered a little, in the post-therapy survey 75% answered the option nothing. General physical state of health, in the item in the item "I feel sick" in the pre-therapy survey 50% answered the option nothing, a remaining answered a little and in the post-therapy survey 63% answered the option nothing. Family and social environment in the item "I am satisfied with the way my family communicates" in the pre-therapy survey 50% answered the option very much, in the post-therapy survey 75% answered the option very much. Personal functioning capacity, in the item "I am satisfied with my current quality of life" in the pre-therapy survey 38% answered the option very much, in the post-therapy survey 38% responded to the option very much.